Pembentukkan sistem pensaizan pakaian remaja perempuan berdasarkan ukuran antropmetri - Mohd Salleh, Naimah; Osman, Syuhaily; Bari, Siti Balkis; Othman, Mumtazah (Kementerian Pendidikan Malaysia, 2013)
To get comfortable dress, individuals need clothing that fits their body. Anthropometric is a measurement method used in creating clothing sizing system. Due to the absence of body size based on body measurements of teenagers in Malaysia, the clothing manufacturing industry has modified clothing size based on body measurements of teens abroad. This raises researcher’s interest to obtain anthropometric measurements among teenagers in Malaysia. The main purpose of this study is to develop clothing sizing system for teenagers based on anthropometric data. Respondents consisted of 207 female students and selected through purposive sampling technique. A total of 33 body measurements were taken using body Measurement Standard. Based on anthropometric data obtained, teenagers clothing standards sizing system was developed. Formation clothing size standard is expected to help teenagers choose the right size that fit them.